Article Hedges vs boosters: Communicative mitigation and enhancement in the genre of dissertation review - Viktorova, Elena Yurievna (Жанры речи, 2023)
The article presents the results of the cross-disciplinary research which focuses on the two types of discourse markers – hedges and boosters and their use in Russian official dissertation reviews. The study is based on reviews of official opponents and external reviewers of PhD theses on linguistics, literary criticism, history, physics, chemistry and medicine. The reviews were borrowed from the online pages of dissertation councils of Russian universities. The qualitative and quantitative analysis of the data proved the gradual nature of hedging and boosting and showed that hedges and boosters frequency depends on the discipline and the author of the review’s gender. It is shown that in the reviews of humanities scholars hedges prevail over boosters, whereas in natural sciences hedges are more frequent. In all disciplines excepting physics men use hedges and boosters more often than women. Moreover, boosters demonstrate a greater dependence in their  frequency on both the discipline and gender whereas the hedges appear more universal in their use in all the reviews under study.